Website-based Academic Performance Monitoring and Evaluation Information System at IAIN Palopo - Rosdiana, Rosdiana; Arifanti, Dwi Risky; Kaimuddin, Kaimuddin; Mukramin, Mukramin (Jurnal Media Elektro, 2025)
The State Islamic Institute of Religion (IAIN) Palopo uses Monitoring and Evaluation (Monev) to evaluate internal performance in all fields based on their respective work programs that have been formulated in Work Meetings. The Monev determined consists of two, namely Academic Monev and non-Academic Monev. The results of monitoring and evaluation are in the form of very valuable information for leaders or office holders to make improvements to all implementations of work programs that have been determined. The design of this website-based Monev information system is limited to academic Monev with the aim of being accessible anytime and anywhere, so that monitoring and checking by leadership can be carried out to measure the quality of the program that has been implemented. The academic monitoring and evaluation that has been designed is limited to PPL/PLP issues, Graduation activities and Implementation of Real Work Lectures (KKN). The implementation of this academic monitoring and evaluation information system makes it easier for clients to respond and respond to work programs that have been implemented so that they can become an evaluation reference for leadership.